2014
DOI: 10.1136/bmjqs-2014-003239
|View full text |Cite
|
Sign up to set email alerts
|

Exploring new avenues to assess the sharp end of patient safety: an analysis of nationally aggregated peer review data

Abstract: Peer review may be a useful tool for HCOs to assess their sharp end clinical performance, particularly safety events related to diagnostic and treatment errors. To address these emerging and largely preventable events, HCOs could consider revamping their existing peer review programmes to enable self-assessment, feedback and improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…For example, many organisations are conducting safety huddles46 and reviews of patient presentations, though we are unaware of any efforts to monitor these sources for diagnosis-related issues. Similarly, we found that peer review may be a useful tool for healthcare organisations when assessing their sharp-end clinical performance, particularly for diagnosis-related safety events 47. However, current peer review systems are inadequate and need to include root cause analysis approaches and performance improvement thinking to detect and address system issues 48.…”
Section: Challenges Of Real-world Diagnostic Error Measurementmentioning
confidence: 89%
See 2 more Smart Citations
“…For example, many organisations are conducting safety huddles46 and reviews of patient presentations, though we are unaware of any efforts to monitor these sources for diagnosis-related issues. Similarly, we found that peer review may be a useful tool for healthcare organisations when assessing their sharp-end clinical performance, particularly for diagnosis-related safety events 47. However, current peer review systems are inadequate and need to include root cause analysis approaches and performance improvement thinking to detect and address system issues 48.…”
Section: Challenges Of Real-world Diagnostic Error Measurementmentioning
confidence: 89%
“…Similarly, we found that peer review may be a useful tool for healthcare organisations when assessing their sharp-end clinical performance, particularly for diagnosis-related safety events. 47 However, current peer review systems are inadequate and need to include root cause analysis approaches and performance improvement thinking to detect and address system issues. 48 This enhancement of existing peer review programmes could greatly improve processes for diagnostic self-assessment, feedback and improvement.…”
Section: Challenges Of Real-world Diagnostic Error Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…The sharing of knowledge was highlighted as a positive part of this project by some participants. Peer review has been shown by others to be useful to shed light on provider-related errors and associated safety concerns, some of which may be modifiable [ 27 ]. This is of course useful for a single primary care unit, but also at an aggregated level to see patterns at, for example, the national level [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Peer review has been shown by others to be useful to shed light on provider-related errors and associated safety concerns, some of which may be modifiable [ 27 ]. This is of course useful for a single primary care unit, but also at an aggregated level to see patterns at, for example, the national level [ 27 ]. In this study all units got suggestions in their written feedback that they felt was at a higher level and not within their scope.…”
Section: Discussionmentioning
confidence: 99%